The inhibitory potential of thai mango seed kernel extract against methicillin-resistant staphylococcus aureus - Pimsumon Jiamboonsri (2018)
Plant extracts are a valuable source of novel antibacterial compounds to combat pathogenic isolates of methicillin-resistant Staphylococcus aureus (MRSA), a global nosocomial infection. In this study, the alcoholic extract from Thai mango (Mangifera indica L. cv. 'Fahlun') seed kernel extract (MSKE) and its phenolic principles (gallic acid, methyl gallate and pentagalloylglucopyranose) demonstrated potent in vitro antibacterial activity against Staphylococcus aureus and 19 clinical MRSA isolates in studies of disc diffusion, broth microdilution and time-kill assays. Electron microscopy studies using scanning electron microscopy and transmission electron microscopy revealed impaired cell division and ultra-structural changes in bacterial cell morphology, including the thickening of cell walls, of microorganisms treated with MSKE; these damaging effects were increased with increasing concentrations of MSKE. MSKE and its phenolic principles enhanced and intensified the antibacterial activity of penicillin G against 19 clinical MRSA isolates by lowering the minimum inhibitory concentration by at least 5-fold. The major phenolic principle, pentagalloylglucopyranose, was demonstrated to be the major contributor to the antibacterial activity of MSKE. These results suggest that MSKE may potentially be useful as an alternative therapeutic agent or an adjunctive therapy along with penicillin G in the treatment of MRSA infections.